(untitled) (Journal of Health Sciences, 2022)
Introduction: The aim of the study was to determine the nitrites and nitrates content in fresh cow’s milk samples from milking machines, and to determine whether their amount is affected by the season of sampling (summer/winter). Methods: The methodology used was analytical transversal method at 2-time points. All milk samples were sampled at milk machines from the City of Zagreb and Zagreb County, during the summer and winter months in 2020. A total of 40 milk samples were sampled, with 20 samples in each monitored period (summer/winter). A high-performance liquid chromatography with a diode array detector was used to identify and quantify concentrations of the nitrate and the nitrite content. The results were processed using descriptive statistics and the statistics of differences. Results: The analysis determined the range of nitrate content from 1.28 mg/kg to 19.71 mg/kg and the range of nitrite content was from 0.49 mg/kg to 3.42 mg/kg in milk samples. The mean result of nitrates in fresh cow’s milk samples in the summer period was 9.12 mg/kg and in the winter period of 3.88 mg/kg. The mean value of nitrite in the summer was 1.23 mg/kg, while the mean value of nitrite in the winter period was 1.48 mg/kg. Conclusion: The research has shown that the nitrate and the nitrite levels in local fresh cow’s milk sampled in milk machines do not exceed the maximum allowable intake. The obtained results confirmed that the amounts of nitrates and nitrites in the milk samples differ significantly during the winter and summer periods and differences are depending on the location of the milk machine.